Risk factors associated with food consumption and food-handling habits for sporadic listeriosis: a case–control study in China from 2013 to 2022 - Yanlin Niu; Weiwei Li; Biyao Xu; Wen Chen; Xiaojuan Qi; Yijing Zhou; Ping Fu; Xiaochen Ma; Yunchang Guo (Emerging Microbes and Infections)
The prevalence of listeriosis in China has been increasing in recent years. Listeriosis primarily spreads through contaminated food. However, the resilient causative organism, Listeria monocytogenes, and its extended incubation period pose challenges in identifying risk factors associated with food consumption and food-handling habits. This study aimed to identify the risk factors associated with food consumption and food-handling habits for listeriosis in China. A matched case–control study (1:1 ratio) was conducted, which enrolled all eligible cases of listeriosis between 1 January 2013 and 31 December 2022 in China. Basic information and possible risk factors associated with food consumption and food-handling habits were collected. Overall, 359 patients were enrolled, including 208 perinatal and 151 non-perinatal cases. Univariate and multivariable logistic analyzes were performed for the perinatal group. For the perinatal and non-perinatal groups, ice cream and Chinese cold dishes were the high-risk foods for listeriosis (odds ratio (OR) 2.09 95% confidence interval (CI): 1.23–3.55; OR 3.17 95% CI: 1.29–7.81), respectively; consumption of leftovers and pet ownership were the high-risk food-handling habits (OR 1.92 95% CI: 1.03–3.59; OR 3.00 95% CI: 1.11–8.11), respectively. In both groups, separation of raw and cooked foods was a protective factor (OR 0.27 95% CI: 0.14–0.51; OR 0.35 95% CI: 0.14–0.89), while refrigerator cleaning reduced the infection risk by 64.94–70.41% only in the perinatal group. The identification of high-risk foods and food-handling habits for listeriosis is important for improving food safety guidelines for vulnerable populations.